Towards smoke-free cars in the Republic of Korea: Evidence from environmental and biochemical monitoring of thirdhand smoke exposure in taxis - Eun Young Park; Min Kyung Lim; Sun Yeol Hong; Jee Eun Oh; Bo Yoon Jeong; E Hwa Yun; Wonho Yang; Do-Hoon Lee (Tobacco Induced Diseases, 2018)
Introduction To evaluate the level of tobacco smoke exposure in taxis in Korea using tobacco specific environmental markers.